An analysis of the Policy of Increasing the Salaries of Government Employees Based on the Framework of Kingdon's Multiple Streams (Case Study of Budget Law 1401) - Seyyed Mojtaba Shahraeini; Heidar Najafi; Seyyedamir Abbaszade; Mahdi Khosravi; Iman Akbari (مدیریت دولتی)
Objective Issues related to public sector human resources management, particularly those concerning service compensation and annual salary increases for employees, are among the most critical decision-making areas for government managers and parliamentarians in the drafting and approval of annual budget laws. These concerns are also a continuous focus for government employees. Consequently, the mechanism and amount of salary increases for government employees, in a fair and proportionate manner, remain a challenging aspect of the interactions between the government, parliament, and other stakeholders. The current research aims to analyze the policy of increasing government employees' salaries within the framework of Kingdon's multiple streams model in the context of the 1401 budget law. Methods The research methodology is based on documentary studies and analysis within the framework of the advocacy coalition framework in policymaking. The necessary information for this study was collected from three primary sources: documents and archival sources, reports, and news and interviews. The documents and archival sources include legal and organizational documents. For data analysis, events related to this policy were interpreted and analyzed using Kingdon's multiple streams framework. Since the primary goal was to analyze this case within the context of the three streams and other focal events, the theoretical concepts of Kingdon's theory served as the main indicators guiding the analysis. Results The research, based on the multiple streams framework, explains that the reduction in taxes for government employees (excluding faculty members and judges) has disproportionately increased the percentage of salary and benefits for higher-income salary groups. A small portion of minimum wage earners were excluded from this statement due to the increase in the minimum wage. For example, employees earning 6 million Tomans in 1400 experienced a 12% net salary increase (after tax deductions), while those earning 32 million Tomans in 1400 saw about a 19% increase. The studies indicate that this unfair policy, which contradicts the prevailing discourse of the legislative and executive branches, was more influenced by the ignorance of policymakers in the government, parliament, and Guardian Council than by the economic and political interests of various stakeholders. Additionally, the findings reveal that although the Majlis Research Center's role as a policy entrepreneur in this area was not successful during the approval phase, its efforts led to the amendment of the policy in the revised 1401 budget law, thereby restoring the rights of national and military employees and retirees. Conclusion Based on the research findings, it is recommended that in future annual budget laws, when considering salary and benefits increases, attention should be paid to the impact of changes in the tax rate on net salary and benefits growth. To address the identified injustices, subsequent salary and benefits increases should combine a fixed percentage and a fixed amount to ensure that the overall percentage increase is higher for employees with lower salaries.